2014
DOI: 10.3164/jcbn.13-85
|View full text |Cite
|
Sign up to set email alerts
|

The behavior of ROS-scavenging nanoparticles in blood

Abstract: Here, we report an interaction between blood and redox nanoparticles, prepared by self-assembly of amphiphilic block copolymers possessing 2,2,6,6-tetramethylpiperidine-N-oxyls as a side chain of hydrophobic segment. When 4-hydroxy-2,2,6,6-tetramethylpiperidine-N-oxyl was added to rat whole blood, its electron spin resonance signal disappeared rapidly. In contrast, the signal from redox nanoparticles remained for a long period of time, indicating that nitroxide radicals were protected in the blood by their com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
23
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 41 publications
0
23
0
Order By: Relevance
“…Thus far, we have confirmed the remarkable therapeutic effect of intravenously administered RNP N for various oxidative stress injuries such as ischemia-reperfusion injuries of the kidney [ 11 ], brain [ 12 ], and heart (Asanuma, et al, submitted for publication), and intracerebral hemorrhage [ 13 ]. Although LMW nitroxide radicals cause severe adverse effects because of internalization in healthy cells and disturbance of the important electron transport chain in mitochondria [ 14 ], redox polymer nanoparticles do not cause adverse effects because of no internalization in healthy cells such as blood cells [ 15 ] and colon mucosal cells [ 16 ]. Since we have already confirmed that RNP N shows an anti-apoptotic effect on amyloid beta-induced cell death in vitro [ 17 ], in this study, we applied RNP N as an orally administered redox polymer nanotherapeutics for the treatment of senescence-accelerated neural dysfunction.…”
Section: Introductionmentioning
confidence: 99%
“…Thus far, we have confirmed the remarkable therapeutic effect of intravenously administered RNP N for various oxidative stress injuries such as ischemia-reperfusion injuries of the kidney [ 11 ], brain [ 12 ], and heart (Asanuma, et al, submitted for publication), and intracerebral hemorrhage [ 13 ]. Although LMW nitroxide radicals cause severe adverse effects because of internalization in healthy cells and disturbance of the important electron transport chain in mitochondria [ 14 ], redox polymer nanoparticles do not cause adverse effects because of no internalization in healthy cells such as blood cells [ 15 ] and colon mucosal cells [ 16 ]. Since we have already confirmed that RNP N shows an anti-apoptotic effect on amyloid beta-induced cell death in vitro [ 17 ], in this study, we applied RNP N as an orally administered redox polymer nanotherapeutics for the treatment of senescence-accelerated neural dysfunction.…”
Section: Introductionmentioning
confidence: 99%
“…However, TEMPOL administration leads to a significant lowering of blood pressure, thus limiting its potential clinical utility [11]. TEM-POL is also internalized in normal cells nonspecifically [9][10][11]. Therefore, we developed a novel way to deliver TEMPO to the site of injury (high ROS production) with minimal exposure to the blood stream, thus reducing TEMPO's side effects.…”
Section: Discussionmentioning
confidence: 99%
“…However, these compounds have not been able to advance to the clinical setting, due in part to problems with their short half-life and several observed side effects [8]. One of the most important issues for low-molecular-weight (LMW) antioxidants such as TEMPOL is that excessive uptake in healthy cells may disrupt normal redox reactions triggering mitochondrial dysfunction and apoptosis [9,10]. It has also been reported that the administration of 2,2,6,6-tetramethylpiperidine-1-oxyl (TEMPO) derivatives, such as TEMPOL, future science group Research Article Eguchi, Yoshitomi, Lazic et al in animals may induce a dramatic reduction in blood pressure [11].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, LMW TEMPO derivatives have been reported to induce mitochondrial dysfunction because they pass through the cell membrane and lead to non‐essential redox reactions. Given that the nanoparticles can suppress its uptake into normal cells unlike LMW compounds, RNPs suppress LMW nitroxide radical‐induced mitochondrial dysfunction . This is one of the reasons for the extremely low toxicity of RNPs both in vivo and in vitro.…”
Section: Safety Of Rnpmentioning
confidence: 99%